Navigating change: agile leadership implementation in local government of Palu City - Sary, Chichi Kumala; Adda, Harnida Wahyuni; Rossanti, Niluh Putu Evvy (Manajemen dan Bisnis, 2024)
This research investigates the implementation of agile leadership within the Palu City government, adopting a constructivist paradigm with a qualitative approach. Data collection was carried out by interviews with seven informants. Data were collected and analyzed using triangulation techniques and MAXQDA-20 software. The findings reveal that the Palu City government successfully integrates agile leadership principles such as adaptability, stakeholder involvement, transparency, and innovation. Notably, these practices have facilitated effective policy implementation, notably in waste management and urban planning, resulting in the attainment of the Adipura Award. Despite challenges posed by natural disasters and pandemics, the government's agile approach has enabled it to effectively navigate crises and maintain service delivery standards. The study underscores the significance of transitioning from traditional "command and control" models to collaborative leadership frameworks, emphasizing adaptability and innovation to tackle complex challenges. Recommendations include further enhancing stakeholder engagement and fostering a culture of agility to bolster government responsiveness and efficiency in addressing societal needs.